Triazole-based cross-linkers in radical polymerization processes: tuning mechanical properties of poly(acrylamide) and poly(N, N-dimethylacrylamide) hydrogels. Issue 60 (10th October 2018) - Götz, Tobias; Schädel, Nicole; Petri, Nadja; Kirchhof, Manuel; Bilitewski, Ursula; Tovar, Günter E. M.; Laschat, Sabine; Southan, Alexander
Abstract : Poly(acrylamide) and poly( N, N -dimethylacrylamide) hydrogels were prepared by free-radical polymerization using triazole-based cross-linkers with different spacer lengths and functional end groups and hydrogel properties were assessed. Abstract : Triazole-based cross-linkers with different spacer lengths and different functional end groups (acrylamides, methacrylamides, maleimides and vinylsulfonamides) were synthesized, investigated for cytotoxic and antibacterial activity, and incorporated into poly(acrylamide) (PAAm) and poly( N, N -dimethylacrylamide) (PDMAAm) hydrogels by free-radical polymerization. Hydrogels prepared with different cross-linkers and cross-linker contents between 0.2% and 1.0% were compared by gel yields, equilibrium degrees of swelling ( S ) and storage moduli ( G ′). Generally with increasing cross-linker content, G ′ values of the hydrogels increased, while S values decreased. The different polymerizable cross-linker end groups resulted in a decrease of G ′ in the following order for cross-linkers with C4 spacers: acrylamide > maleimide > methacrylamide > vinylsulfonamide. Longer cross-linker alkyl spacer lengths caused an increase in G ′ and a decrease in S . Independent of the cross-linker used, a universal correlation between G ′ and equilibrium polymer volume fraction ϕ was found. For PAAm hydrogels, G ′ ranged between 4 kPa and 23 kPa and ϕ between 0.07 and 0.14. For PDMAAm hydrogels, G ′ ranged between 0.1 kPa and 4.9 kPa and ϕ between 0.02 and 0.06. The collected data were used to establish an empirical model to predict G ′ depending on ϕ . G ′ of PAAm and PDMAAm hydrogels is given by G ′ = 4034 kPa ϕ 2.66 and G ′ = 4297 kPa ϕ 2.46, respectively.